[18F]-AV-1451 binding in the substantia nigra as a marker of neuromelanin in Lewy body diseases. Issue 3 (28th August 2021) - Mak, Elijah; Kouli, Antonina; Holland, Negin; Nicastro, Nicolas; Savulich, George; Surendranathan, Ajenthan; Malpetti, Maura; Manavaki, Roido; Hong, Young T; Fryer, Tim D; Aigbirhio, Franklin; Rowe, James B; et al.
Abstract: While [ 18 F]-AV-1451 was developed as a PET radiotracer with high affinity for hyperphosphorylated tau, it has been proposed that loss of 'off-target' [ 18 F]-AV-1451 binding to neuromelanin in the substantia nigra could be a surrogate marker of Lewy body diseases. [ 18 F]-AV-1451 binding was measured in the substantia nigra of patients with Parkinson's disease ( n = 35), dementia with Lewy bodies ( n = 10) and separate control groups ( n = 37; n = 14). Associations with motor symptoms, cognition and disease duration were evaluated using linear regression models. The dementia with Lewy bodies group had significantly reduced substantia nigra [ 18 F]-AV-1451 binding compared to controls after adjusting for age ( P < 0.05). However, there were no significant differences in substantia nigra [ 18 F]-AV-1451 binding between Parkinson's disease and controls. Substantia nigra [ 18 F]-AV-1451 binding was not associated with age, disease duration, Movement Disorders Society—Unified Parkinson's Disease Rating Scale and cognitive scores in dementia with Lewy bodies and Parkinson's disease groups. Despite the reduction of substantia nigra [ 18 F]-AV-1451 binding in dementia with Lewy bodies, these findings suggest that substantia nigra [ 18 F]-AV-1451 binding has no value as a diagnostic marker in early Parkinson's disease. Further investigations in longitudinal cohorts are warranted. Graphical abstract: Abstract : Mak and Kouli et al. evaluated [ 18 F]-AV-1451 uptake of the substantia nigra in dementia with Lewy bodies and Parkinson's disease patients. The findings do not strongly support [ 18 F]-AV-1451 as a marker of pigmented neurons loss in the substantia nigra. Further longitudinal investigations in Lewy body diseases cohorts are warranted.